Clinical significance of interval changes in breast lesions initially categorized as probably benign on breast ultrasound. Issue 12 (March 2017) - Jang, Ja Yoon; Kim, Sun Mi; Kim, Jin Hwan; Jang, Mijung; La Yun, Bo; Lee, Jong Yoon; Lee, Soo Hyun; Kim, Bohyoung
Abstract : Abstract: The aims of this study were to determine the malignancy rate of probably benign lesions that show an interval change on follow-up ultrasound and to evaluate the differences seen on imaging between benign and malignant lesions initially categorized as probably benign but with interval change on follow-up breast ultrasound. We retrospectively reviewed 11, 323 lesions from ultrasound-guided core-biopsies performed between June 2004 and December 2014 and identified 289 lesions (266 patients) with an interval change from probably benign (Breast Imaging Reporting and Data System [BI-RADS] category 3) in the previous 2 years. Malignancy rates were compared according to the ultrasound findings and the characteristics of the interval changes, including changes in morphology and/or diameter. The malignancy rate for probably benign lesions that showed an interval change on follow-up ultrasound was 6.9% (20/289). The malignancy rate was higher for clustered cysts (33.3%) and irregular or noncircumscribed masses (12.7%) than for circumscribed oval masses (5%) or complicated cysts (5%) seen on initial ultrasound ( P  = 0.043). Fifty-five percent of the malignancies were found to be ductal carcinoma in situ and there was 1 case of lymph node metastasis among the patients with invasive disease in whom biopsy was delayed by 6 to 15 months. The extent of invasiveness was greater in missed cases. There was a significant difference in the maximal diameter change between the 20 malignant lesions and the 269 benign lesions (4.0 mm vs 2.7 mm, P  = 0.002). The cutoff value for maximal diameter change per initial diameter was 39.0% for predicting malignancy (sensitivity 95%, specificity 53.5%). The malignancy rate for morphologically changed lesions was significantly higher than for morphologically stable lesions (13.6% vs 4.9%; P  = 0.024) Our 6.9% of probably benign lesions that showed an interval change finally turned out to be malignancy was mostly DCIS. The sonographic features, interval changes in sonographic features, and lesion size might help in the recategorization of these lesions.